Impact of Petroleum Energy Price Volatility on Commodity Prices in Ghana - Dadzie, Philomena; Nambie, Nicholas Bamegne; Obobi, Belinda Ameh (International Journal of Economics and Financial Issues, 2023)
The purpose of this article is to demonstrate the relationship between petroleum energy volatility and commodity prices in Ghana, which are indexed (energy grains, meat, and cooking oil), as well as to provide an empirical specification of the impact’s direction. With reference to time series literature, the paper examined energy and commodity price connection models such as augmented dickey fuller, granger causality, co-integration, vector autoregressive and the vector error correction models used in estimating the association among petroleum energy volatility and the three selected commodity variables. The paper found that, there is a long run relationship between petroleum energy volatility and commodity prices in Ghana from 2011 to 2022. A single equation error correction model suggested that, petroleum energy shocks increase prices of grains, meat and cooking oil in both the short and long run. Impulse response function and variance decomposition conducted on the variables also suggested that there is both short and long run association between the variables.